Orson Welles the road to Xanadu - Callow, Simon 1949- (Viking Penguin, 1996)
Traces the life and career of the legendary director, discussing the making of "Citizen Kane," his contributions to such films as "The Magnificent Ambersons" and "The Lady from Shanghai," and his efforts in radio comedy, spectacular theater, and newspaper politics.
Filmogr. S. 584. - Bibliogr. S. 611 - 614
Keywords: Welles, Orson <1915-1985>; Welles, Orson -- 1915-1985; Actors -- United States -- Biography; Motion picture producers and directors -- United States -- Biography; USA; Biografie